Re‐Emergence of Poliovirus in the United States: Considerations and Implications. Issue 5 (6th October 2022) - Russo, Grace B.; Goyal, Tarini; Tyler, Kenneth; Thakur, Kiran T.
Abstract : The first case of paralytic poliomyelitis in nearly a decade in the US was discovered in a 20‐year‐old unvaccinated man from Rockland County, New York, in July 2022, who developed acute flaccid myelitis. The isolated virus from stool sampling was found to be a circulating vaccine‐derived poliovirus type 2, derived from the oral polio vaccine. Since the discovery of this case, local wastewater surveillance has revealed evidence of circulating vaccine‐derived poliovirus type 2 in local counties, as well as in New York City, representing community transmission. In the wake of the coronavirus disease 2019 pandemic, routine vaccination administration has declined globally, with increasing numbers of communities not vaccinated for poliovirus. Now, with evidence of local community transmission, the clinical implication for at‐risk unvaccinated individuals is significant. Here, we review the epidemiological origin of this discovered strain of poliovirus, national and international methods of surveillance for poliovirus, and neurological features of poliovirus. We also highlight the opportunities and challenges involved in monitoring suspected cases, as well as the unique role neurologists might play in national and global poliomyelitis surveillance. ANN NEUROL 2022;92:725–728